Evaluation of growth and development of patients with Down syndrome in Santiago de Cuba - Tamara Rubio González; Lisandra Norbert Vázquez; Dianelys de la Caridad García González (Centro Provincial de Información de Ciencias Médicas, 2018)
A descriptive, cross-sectional and quantitative study of 54 patients with Down syndrome, assisted in the Clinical Genetics Service of "Dr. Antonio María Béguez César" Teaching Southern Children Hospital was carried out in Santiago de Cuba, from 2000 to 2015, aimed at determining the growth pattern of those affected patients. Among the analyzed variables there were age, sex and anthropometric indexes: weight according to age, height according to age, weight/height index and body mass index; also, the most frequent congenital defects were evaluated in the sample. It was concluded that the growth pattern of these patients is similar to the one described in the medical literature related to the topic, which can be useful for the clinical care that should be offered, as well as to guide the parents on the eating habits and lifestyles as part of the treatment of children and adolescents with this syndrome.